Role of indacaterol, a once-daily bronchodilator, in chronic obstructive pulmonary disease - Seth, Heemesh D. (Pioneer Bioscience Publishing Company, 2013)
Chronic obstructive pulmonary disease (COPD) is characterized by progressive airflow obstruction that can lead to lung destruction and dyspnea. Although there has been a slight reduction in mortality in recent decades, COPD is still a serious health problem that has enormous costs and utilizes significant medical resources. There have been a number of pharmacologic interventions that have been developed for the treatment of COPD. Current guidelines recommend the use of long-acting bronchodilators for the treatment of moderate and severe stage COPD, since they have been shown to improve lung function, respiratory symptoms, and quality of life. Indacaterol is a once-daily beta2-agonist (β2-agonist) delivered by a single-dose dry powder inhaler used for the treatment of COPD. It is currently approved at a dose of 75 μg in the United States and a dose of 150 μg with a maximal dose of 300 μg in Europe and other countries. Several studies show that indacaterol was statistically superior to both long-acting β2-agonist, formoterol and salmeterol, as well as, noninferior to tiotropium. Indacaterol is generally well tolerated and has a good safety profile. Other studies show that there is an additive bronchodilator response with the addition of indacaterol to tiotropium, which would provide a once-daily treatment option for patient with moderate to severe COPD. This review discusses the pharmacokinetic, comparative efficacy and safety data for indacaterol.